The Effect of Probing Prompting Learning Model with Geoboard Media on Fourth-Grade Mathematics Learning Outcomes - Puspita, Nyoman Asih (International Journal of Elementary Education, 2024)
The lack of students’ understanding during mathematics learning requires teachers to focus on using appropriate learning models. This study aims to determine the effect of the probing prompting learning model assisted by geoboard media on the mathematics learning outcomes of fourth-grade public elementary school students. This research employed a quantitative method with a quasi-experimental design in the form of a post-test-only control group design. The study population consisted of 514 fourth-grade students. Samples were selected using cluster random sampling, resulting in an experimental class of 30 students and a control class of 29 students from two different schools. Data were collected using a multiple-choice test instrument. The research data were analyzed using inferential statistical techniques (t-test) with pooled variance. The results showed that the average post-test score in the experimental class was 88.33, categorized as high, while the control class scored 70.69, categorized as moderate, based on the five-point evaluation scale. The t-test analysis revealed tcount = 9.255 and ttable = 2.002 at a 5% significance level with df = 57, showing tcount > ttable. This indicates a significant difference in mathematics learning outcomes between students taught using the probing prompting model assisted by geoboard media and those who were not. In conclusion, the probing prompting learning model assisted by geoboard media significantly influences the mathematics learning outcomes of fourth-grade elementary school students, making it a viable innovative learning model for teachers and a subject for further research in education.